Adipokines: mediators of immunity and inflammation - Kharbanda, Rajat; Bansal, Tarun (International Journal of Research in Medical Sciences, 2020)
White adipose tissue has emerged as a highly dynamic organ that releases a plethora of immune and inflammatory mediators that are involved in obesity, metabolic syndrome and immune mediated diseases. Adipokines have complex role in various physiological and pathological processes by exerting potent modulatory actions on target tissues In this Review, In this review, we explore the effects of different adipokines, focusing primarily on leptin, adiponectin, visfatin and resistin in causing immune-mediated and/or inflammatory diseases.